Intratumoral and Peritumoral Apparent Diffusion Coefficient and MGMT mRNA Expression in Different Meningioma Histopathological Grade - Rahmad Mulyadi; Mochamma Hatta; Andi Asadul Islam; Bachtiar Murtala; Jumraini Tammase; Muhammad Firdaus; Eka Susanto; Joedo Prihartono (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Histopathological examination is the gold standard for diagnosing meningioma and determining the treatments. However, it is invasive in nature. This study was conducted to identify intratumoral and peritumoral apparent diffusion coefficient (ADC) value and mRNA O6-methylguanine-DNA methyltransferase (MGMT) expression in meningioma.METHODS: Data were collected from 39 patients who were clinically diagnosed with meningioma. However, only 37 patients met the inclusion criteria. These subjects then underwent examinations and received treatment from October 2017 to September 2018. Magnetic resonance imaging (MRI) data with diffusion-weighted imaging-apparent diffusion coefficient (DWI-ADC) sequence, histopathological diagnosis of meningioma, and results of MGMT mRNA expression were obtained.RESULTS: The most frequent type of low-grade and overall tumor was meningioma not otherwise specified (56.8%). For high-grade tumor, there were two atypical cases: atypical meningioma (2.7%) and rhabdoid meningioma (2.7%). Meningothelial meningioma had the highest mean value of minimum intratumoral ADC at 864.57±219 x10-3 mm2/s, whereas rhabdoid meningioma had the lowest at 417 x10-3 mm2/s. For minimum peritumoral ADC, rhabdoid meningioma had the highest mean value at 1,651 x10-3 mm2/s, while atypical meningioma has the lowest at 1,281 x10-3 mm2/s. For MGMT mRNA, meningothelial meningioma had the highest mean value at 10±1.2 fold change, whereas rhabdoid meningioma had the lowest mean at 6.18 fold change.CONCLUSION: WHO grade I meningiomas had higher minimum intratumoral ADC values and higher MGMT mRNA expression than the high-grade tumors. Minimum peritumoral ADC values differed across the histopathological grades.KEYWORDS: meningioma, RNA, messenger, MRI, methyltransferases, RT-PCR, ADC, MGMT mRNA